54.1k views
2 votes
4√2 + √2 with work

8√3 - 4√3 with work

2√3 x √32 with work

2 Answers

5 votes

Answer:

1.
5√(2)

2.
4√(3)

3.
8√(6)

Explanation:

Number 1:

We can treat
√(2) as a variable in which we are multiplying 4 by. Let's call
√(2) x.

This makes our expression
4x + x. Combining like terms, we get
5x. This means that
4√(2) + √(2) = 5√(2).

Number 2:

Again, we can use the same logic as we did in number 1. Let's treat
√(3) as a variable y.


8y-4y

Subtracting a y term from a y term will equal the difference between the coefficients times y. So it's
4y. This means that
8√(3)-4√(3)=4√(3)

Number 3:

When we multiply radicals, we want to put the radicals in
√(x) form.


√(32) is already in this form.

However
2√(3) is not.


2√(3) is the same thing as
√(3\cdot2^2) = √(3\cdot4) = √(12).

Now we multiply these radicals by multiply the term inside the square root sign


√(32)\cdot√(12)=√(32\cdot12) =√(384)

384 is divisible by 64, so:


√(384) = √(64\cdot6) = 8√(6)

Hope this helped!

User Moose Morals
by
5.0k points
1 vote

Explanation:

4√2 + √2 = 5√2 we add 4 and the invisible 1 in front of √2, the common root stays same

8√3 - 4√3 = 4√3 subtract 4 from 8 the common root stays same

2√3 x √32 ➡ 2√3 x 4√3 too add the expressions we first need to make the roots common then add 4 and 2

User Knuckfubuck
by
4.7k points